The relationship between Lp(a) and CVD outcomes: a systematic review. Issue 1 (December 2016) - Forbes, Carol; Quek, Ruben; Deshpande, Sohan; Worthy, Gill; Wolff, Robert; Stirk, Lisa; Kleijnen, Jos; Gandra, Shravanthi; Djedjos, Stephen; Wong, Nathan
Abstract Robust associations between lipoprotein(a) [Lp(a)] and CVD outcomes among general populations have been published in previous studies. However, associations in high risk primary prevention and secondary prevention populations are less well defined. In order to investigate this further, a systematic review was performed including prospective studies, which assessed the relationship between Lp(a) and CVD outcomes using multivariable analyses. Additional information was gathered on Lp(a) assays, multivariable modelling and population characteristics. Literature searches from inception up to December 2015 retrieved 2850 records. From these 60 studies were included. Across 39 primary prevention studies in the general population (hazard ratios ranged from 1.16 to 2.97) and seven high risk primary prevention studies (hazard ratios ranged from 1.01 to 3.7), there was evidence of a statistically significant relationship between increased Lp(a) and an increased risk of future CVD. Results in 14 studies of secondary prevention populations were also suggestive of a modest statistically significant relationship (hazard ratios ranged from 0.75 to 3.7). Therefore current evidence would suggest that increased Lp(a) levels are associated with modest increases in the risk of future CVD events in both general and higher risk populations. However, further studies are required to confirm these findings.